Student's Decision to Choose University: Building Brand Image - Widiastuti, Erni (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
The purpose of this study was to analyze the dimensions of brand image to strengthen the student's decision to choose a private university. The research method used is a qualitative method with a literature study of several journals related to this issue. Based on the results of previous journal discussions, it is known that brand image is the added value or incremental utility of a product given through its brand name which is determined by the dimensions of the brand image, namely product quality, brand loyalty, and brand associations. So the image is formed based on the impression that a person feels about an educational institution.